2005
DOI: 10.1080/17450390512331387954
|View full text |Cite
|
Sign up to set email alerts
|

The influence of associative effects on thein vitro-estimated utilizable crude protein (uCP) of feeds for ruminants

Abstract: Nineteen feed mixtures, formulated with 16 single feeds, were used to study the influence of associative effects on utilizable crude protein (uCP) of feed mixtures. The in vitro incubation technique of Zhao and Lebzien (2000) was used for uCP determination. It was found that the in vitro-determined uCP (D-uCP) was significantly higher than the weighted uCP (W-uCP) of feed mixtures and there was a significant regressive relationship between W-uCP (x) [g x kg(-1)DM] and D-uCP (y) [g x kg(-1)DM]: y=(0.94 +/- 0.23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
2
1
Order By: Relevance
“…Due to the small variability between feeds and only eight data points for regression analysis, this systematical overestimation should be interpreted with caution and reference to their biological and practical relevance, which seems negligible. This contrasts with the findings of Zhao et al (2005), who reported higher differences between calculated and observed uCP values in an experiment using 16 single feeds and 19 mixtures. They noted statistically significant and nonsystematic differences between calculated and observed uCP values.…”
Section: Additivity Of Ruminal Fermentation Characteristics and Feeding Valuescontrasting
confidence: 99%
See 2 more Smart Citations
“…Due to the small variability between feeds and only eight data points for regression analysis, this systematical overestimation should be interpreted with caution and reference to their biological and practical relevance, which seems negligible. This contrasts with the findings of Zhao et al (2005), who reported higher differences between calculated and observed uCP values in an experiment using 16 single feeds and 19 mixtures. They noted statistically significant and nonsystematic differences between calculated and observed uCP values.…”
Section: Additivity Of Ruminal Fermentation Characteristics and Feeding Valuescontrasting
confidence: 99%
“…They noted statistically significant and nonsystematic differences between calculated and observed uCP values. However, the authors mentioned the possibility of incomplete incubation of some feeds due to incomplete mixing with the incubation liquid (Zhao et al, 2005). Such an effect was avoided in the present study by the constant motion of the rotary incubator.…”
Section: Additivity Of Ruminal Fermentation Characteristics and Feeding Valuesmentioning
confidence: 82%
See 1 more Smart Citation